2007
DOI: 10.1109/tits.2007.908562
|View full text |Cite
|
Sign up to set email alerts
|

Variable Speed Limits: Safety and Operational Impacts of a Candidate Control Strategy for Freeway Applications

Abstract: Variable Speed Limit Sign (VSLS) systems enable transportation managers to dynamically change the posted speed limit in response to prevailing traffic and/or weather conditions. Although VSLS have been implemented in a limited number of jurisdictions throughout the world there is currently very limited documentation describing the quantitative safety and operational impacts. Furthermore, the impacts reported are primarily from systems in Europe, and may not be directly transferable to other jurisdictions, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(85 citation statements)
references
References 7 publications
4
79
0
2
Order By: Relevance
“…Intelligent speed adaptation [10] and variable speed limit sign systems [1] have increasingly gained attention as a means to increase road traffic safety. Related research in these areas, however, (i) focuses on experiments and simulations of traffic behavior [4], [5] and models for determining optimal speed limits [11], (ii) shows the effectiveness of speed adaptation in terms of reducing casualties [1], [12], homogenizing speed [3], increasing compliance with speed limits [10], as well as (iii) discusses impacts on travel time and throughput. We, instead, investigate constraints that implementations of such a system must respect and verify the safety that can be guaranteed under these constraints.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Intelligent speed adaptation [10] and variable speed limit sign systems [1] have increasingly gained attention as a means to increase road traffic safety. Related research in these areas, however, (i) focuses on experiments and simulations of traffic behavior [4], [5] and models for determining optimal speed limits [11], (ii) shows the effectiveness of speed adaptation in terms of reducing casualties [1], [12], homogenizing speed [3], increasing compliance with speed limits [10], as well as (iii) discusses impacts on travel time and throughput. We, instead, investigate constraints that implementations of such a system must respect and verify the safety that can be guaranteed under these constraints.…”
Section: Related Workmentioning
confidence: 99%
“…A typical application of intelligent speed adaptation with variable speed limits is to lower and homogenize speed in the area of traffic incidents [1]. For example, Lu et al [8] use variable speed limit control to maximize bottleneck flow in an area of a lane drop, such as encountered when lanes merge or lanes are closed due to road work.…”
Section: Challenges In Intelligent Speed Adaptationmentioning
confidence: 99%
See 2 more Smart Citations
“…The control logic, threshold values and detector-controller layout applied to speed limiters are considered to a partially determinant factor for success of VSL (Li et al, 2015;Allaby et al, 2007). Li et al (2014) proposed some modifications to detector location and control logic for the logic tree based VSL control algorithm proposed by Allaby et al (2007) which is implemented in a critical section of Auckland Motorway using AIMSUN micro-simulator. They concluded that the performance of VSL is highly dependent on the control logic embedded and on the location of the VSL detectors.…”
Section: Introductionmentioning
confidence: 99%